RoomAlive: Magical Experiences Enabled by Scalable, Adaptive Projector-Camera Units - Jones, Brett; Sodhi, Rajinder; Murdock, Michael; Mehra, Ravish; Benko, Hrvoje; Wilson, Andy; Ofek, Eyal; MacIntyre, Blair; Raghuvanshi, Nikunj; Shapira, Lior (UIST '14 Proceedings of the 27th annual ACM symposium on User interface software and technology, 2014)
RoomAlive is a proof-of-concept prototype that transforms any room into an immersive, augmented entertainment experience. Our system enables new interactive projection mapping experiences that dynamically adapts content to any room. Users can touch, shoot, stomp, dodge and steer projected content that seamlessly co-exists with their existing physical environment. The basic building blocks of RoomAlive are projector-depth camera units, which can be combined through a scalable, distributed framework. The projector-depth camera units are individually autocalibrating, self-localizing, and create a unified model of the room with no user intervention. We investigate the design space of gaming experiences that are possible with RoomAlive and explore methods for dynamically mapping content based on room layout and user position. Finally we showcase four experience prototypes that demonstrate the novel interactive experiences that are possible with RoomAlive and discuss the design challenges of adapting any game to any room.